ANALYSIS OF COFFEE EXPORT COMPETITIVENESS IN CENTRAL JAVA PROVINCE 2014-2019 - Wahyuningsih, Sri; Wibowo, Hendri; Hastuti, Dewi; Wilantika, Linda (Universitas Wahid Hasyim, 2022)
Coffee as excellent commodity and the second largest traded commodity in the world has enormous market potential in both international and domestic markets. Central Java is one of the national coffee producer provinces which is considered to have a good coffee quality and is not inferior to other superior coffee. The aim of this study was to determine the potential and trend of export competitiveness of Central Java coffee. This research used descriptive analysis method as the basic method and used secondary data. The analytical methods used in this research are RCA (Revealed Comparative Advantage) and ECI (Export Competitiveness Index). The results showed that the average value of the competitiveness of Central Java coffee exports for the 2014-2019 period showed an average value of RCA < 1, which was 0,29. These results indicated that the Central Java coffee commodity has a weak comparative competitiveness. Meanwhile, the ECI analysis showed that Central Java coffee for the 2014-2019 period has an average value of ECI > 1, which is 1,29. These results indicated that Central Java coffee has strong competitive competitiveness and tends to have an increasing trend of competitiveness.Keywords: Coffee; Competitiveness; ECI; RCA